2010
DOI: 10.1523/jneurosci.5286-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of a Segmental Switch Enables Corticospinal Tract Transmission to Spinal Forelimb Motor Circuits

Abstract: Development of skilled movements and the corticospinal tract (CST) begin prenatally and continue postnatally. Because the CST is required for skilled movements in maturity, it is accepted that motor skills cannot occur until the CST develops a mature organization. We recently showed that the CST plays an essential role in postnatal development of interneurons comprising the spinal circuits it engages. We proposed that CST signals are more effectively transmitted to ventral motor circuits after interneuron matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…Some improvements in motor skill can be driven by existing motor networks, while more robust changes in motor skill are associated with rewiring of motor pathways 51 . It is also likely that plasticity occurred in brain regions other than M1, such as secondary motor areas, sensory networks 52-54 , subcortical brain structures 55 , and spinal interneuronal systems 2,37,56 . It is likely that plasticity in these systems underlies the motor improvements seen in the unstructured practice group.…”
Section: Discussionmentioning
confidence: 99%
“…Some improvements in motor skill can be driven by existing motor networks, while more robust changes in motor skill are associated with rewiring of motor pathways 51 . It is also likely that plasticity occurred in brain regions other than M1, such as secondary motor areas, sensory networks 52-54 , subcortical brain structures 55 , and spinal interneuronal systems 2,37,56 . It is likely that plasticity in these systems underlies the motor improvements seen in the unstructured practice group.…”
Section: Discussionmentioning
confidence: 99%
“…There were few examples in the literature that provided insights on the possibility that neurons could switch to a different neurotransmitter in the mammalian system following activity/photoperiod manipulation. Neurons of the cervical spinal cord in cats display this type of recruitment for the cholinergic phenotype during development (Chakrabarty and Martin, 2010; Chakrabarty et al, 2009). The authors of these studies found that extensive circuit activation of the corticospinal tract affects the total number of ChAT-expressing neurons during a two-week period.…”
Section: Key Studies Investigating Cycling/switching Into Other Stmentioning
confidence: 99%
“…Activity-dependent recruitment of cholinergic neurons occurs similarly during development of the cervical spinal cord in cat (Chakrabarty et al, 2009; Chakrabarty and Martin, 2010). In this system, activity of the corticospinal tract induces a rapid increase in the number of ChAT-positive neurons during a two-week period.…”
Section: Recruitment Of Reserve Pool Neuronsmentioning
confidence: 99%